Incremental approach for the life-cycle greenhouse gas analysis of carbon capture and utilization. (November 2022) - Yoo, Eunji; Lee, Uisung; Zang, Guiyan; Sun, Pingping; Elgowainy, Amgad; Wang, Michael
Abstract: Electro-fuels (e-fuels) are examples of carbon capture and utilization (CCU) hydrocarbon products that are derived from captured carbon dioxide (CO2 ), while using renewable electricity as the energy feedstock. The environmental impacts of CCU products (e.g., e-fuel) are systematically quantified through life-cycle analysis (LCA). Previous studies evaluating LCA of e-fuels proposed frameworks with an expanded system boundary approach that included the entire supply chain of the production process generating the CO2 for CCU, in addition to the supply chain of the CCU product. This expanded system boundary approach evaluates two system boundaries, and uses deduction methods to calculate the carbon intensity (CI) of the CCU product (e-fuel). This paper proposes a simpler system boundary using an incremental approach that can calculate identical CI of the CCU product (e-fuel), while avoiding the extensive calculations in the expanded system boundary framework. The proposed incremental approach allocates the burdens of the CO2 capturing process to the CO2 feedstock supplying the CCU production process (e.g., e-fuel production). The CI of the captured CO2 supplied to CCU process is determined by the energy and material requirements for the CO2 capturing process and transportation to the CCU plant. Thus, the CI of CO2 supplied to CCU process can be directly linked to the CI of e-fuel without the need to conduct LCA of the preceding process that generates the CO2 for CCU. Highlights: Incremental approach provides the carbon intensity of e-fuel through the life-cycle analysis. This approach can avoid extensive calculation for the upstream and downstream processes of CO2 sources. Carbon intensity of CO2 feedstock is determined by energy consumption burden for CO2 capture. Incremental approach evaluates the impact of various CO2 sources for the same CCU technology.